The first survey of Cystobasidiomycete yeasts in the lichen genus Cladonia; with the description of Lichenozyma pisutiana gen. nov., sp. nov - Černajová, Ivana; Škaloud, Pavel (Fungal biology, 2019)
The view of lichens as a symbiosis only between a mycobiont and a photobiont has been challenged by discoveries of diverse associated organisms. Specific basidiomycete yeasts in the cortex of a range of macrolichens were hypothesized to influence the lichens' phenotype. The present study explores the occurrence and diversity of cystobasidiomycete yeasts in the lichen genus Cladonia. We obtained seven cultures and 56 additional sequences using specific primers from 27 Cladonia species from all over Europe and performed phylogenetic analyses based on ITS, LSU and SSU rDNA loci. We revealed yeast diversity distinct from any previously reported. Representatives of Cyphobasidiales, Microsporomycetaceae and of an unknown group related to Symmetrospora have been found. We present evidence that the Microsporomycetaceae contains mainly lichen-associated yeasts. Lichenozyma pisutiana is circumscribed here as a new genus and species. We report the first known associations between cystobasidiomycete yeasts and Cladonia (both corticate and ecorticate), and find that the association is geographically widespread in various habitats. Our results also suggest that a great diversity of lichen associated yeasts remains to be discovered.
Keywords: lišejníky; Basidiomycota; Ecosystem; symbióza; Lichens; ekosystém; fylogeneze; Symbiosis; Evropa; Phylogeny; Europe